Volatile organic compounds profile of Lactobacillus casei and Streptococcus thermophilus in fermented mare milk of Kazakhstan (International Journal of Biology and Chemistry, 2018)
Fermented milk is a common beverage in many countries, but its flavor is highly variable from one region to another. The fermented mare milk, common beverage in Central Asia, has a typical flavor of koumiss, but those flavors were never described using aroma compound determination. In the present study,six lactic acid bacteria were identified in local koumiss. Due to the apparent technological advantage of Lactobacillus casei and Streptococcus thermophilus (notably their acidification speed), the main objective of this study was to compare their volatile compound profiles. 35 aromatic compounds were detected. Tocompare the aroma profiles of each strain, the ratio proportion strain/control was calculated for each strain and for each aroma showing significantly different profiles with predominance of 2-methyl-1-propanol and 2-undecanol in milk fermented with L. casei, and of 2,3-pentanedione in milk fermented with S.thermophilus. L. casei strain produced more aroma and its profile was significantly (P>0.03) different from S. thermophilus profile.